Perancangan Digital Bisnis Pada UMKM Fotocopy Mitra Abadi - Septria Maharani; Nanda Wijaya; Laras Triana; Raihan Muhammad Satrio; Faradika (CV. ITTC INDONESIA, 2024)
Rapid advancements in information and communication technology, particularly in the digital era, have significantly transformed the business landscape. Micro, Small, and Medium Enterprises (MSMEs) are crucial sectors that need to adapt quickly to remain competitive and thrive amid intensifying competition. Digital transformation has become imperative for MSMEs to optimize the vast potential and market opportunities in the online world. Facing challenges in the digital era, Fotocopy Mitra Abadi, a small business in the Services and Trade sector, strives to enhance its visibility and accessibility. The ubiquity of the internet and mobile devices in people's daily lives underscores the importance for MSMEs to establish a robust digital presence. One strategic approach is the development of a website—a collection of interconnected pages accessible worldwide via the internet. A website, comprising text, images, sound, and animations, becomes an engaging information medium for visitors. Recognizing these necessities, this website development project is initiated to provide solutions for Fotocopy Mitra Abadi in harnessing digital potential to expand market share, connect with customers, and create a more efficient and enjoyable shopping experience. The Digital Business course provides an opportunity for us, as students, to apply contemporary web design concepts and technologies tailored to the needs and characteristics of Fotocopy Mitra Abadi's business. Through this project, we aim to make a positive contribution to supporting the growth and sustainability of this MSME in the digital era. With this background, this report outlines the steps, processes, and the final outcome of the website development project for Fotocopy Mitra Abadi. Hopefully, the resulting website will serve as an effective tool in enhancing Fotocopy Mitra Abadi's digital presence and competitiveness in the Services and Trade market..